2018
DOI: 10.1002/jlb.3mia0917-352r
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 knockout of USP18 enhances type I IFN responsiveness and restricts HIV-1 infection in macrophages

Abstract: The IFN-stimulated gene ubiquitin-specific proteinase 18 (USP18) encodes a protein that negatively regulates T1 IFN signaling via stearic inhibition of JAK1 recruitment to the IFN-α receptor 2 subunit (IFNAR2). Here, we demonstrate that USP18 expression is induced by HIV-1 in a T1 IFN-dependent manner. Experimental depletion of USP18 by clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) gene editing results in a significant restriction of HIV-1 replication in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 79 publications
3
51
0
Order By: Relevance
“…These data strongly support a mechanistic model, wherein interferon beta drives the anti-inflammasome and inhibits the inflammasome module through activation of immune suppressors, including Usp18, implicating interferon beta as a potential suppressor of immune activity in the chronic phase of neurodegenerative tauopathies ( Fig. 4E), similar to what has been reported in chronic viral infections 62,65,66 .…”
Section: Identification Of the Inflammasome And Anti-inflammasome Relsupporting
confidence: 85%
See 1 more Smart Citation
“…These data strongly support a mechanistic model, wherein interferon beta drives the anti-inflammasome and inhibits the inflammasome module through activation of immune suppressors, including Usp18, implicating interferon beta as a potential suppressor of immune activity in the chronic phase of neurodegenerative tauopathies ( Fig. 4E), similar to what has been reported in chronic viral infections 62,65,66 .…”
Section: Identification Of the Inflammasome And Anti-inflammasome Relsupporting
confidence: 85%
“…Several features of the anti-inflammasome module suggest it too may represent aspects of interferonmediated immunosuppression, including its anti-correlation with the inflammasome module, and its inclusion of genes that function as immune checkpoints (Cd274 (PDL1), Il10rb, Lag3) 54,56-58 and inhibitors of immune activity (Usp18 59-62 , Nfkbiz, Nfkbia, Nfkbie, Tgfbr2 63,64 ). Among these genes is Usp18, an established negative feedback suppressor of type 1 interferon anti-viral immune activity [59][60][61][62]65,66 that is also highly connected with the anti-inflammasome module in microglia treated with interferon-beta ( Supplementary Fig. 4G).…”
Section: Identification Of the Inflammasome And Anti-inflammasome Relmentioning
confidence: 99%
“…KEYWORDS THP-1, USP18, human immunodeficiency virus 1 (HIV-1), p21, restriction factor C ellular antiretroviral restriction factors are an important component of the innate immune response against HIV-1 (1)(2)(3). Many of these proteins are induced or activated by interferons (IFNs) (4)(5)(6).…”
mentioning
confidence: 99%
“…Experimental knockout of USP18 enhances JAK/STAT (signal transducer and activator of transcription) signaling and increases ISGs with elevated levels of protein ISGylation, thus providing resistance to viral infections (3,42,43,52). Recent work by Honke et al (49) showed in 2012 that high expression of USP18 in murine CD169 ϩ macrophages in the splenic marginal zone was required to enforce a local replication of vesicular stomatitis virus (VSV), a negative-sense, single-stranded enveloped RNA virus belonging to the family Rhabdoviridae.…”
mentioning
confidence: 99%
“…Buffy coats were obtained from Life South Community Blood Center (Gainesville, FL) under approval by the Institutional Review Board at the University of Florida. PBMCs were processed as previously described 54 and CD4 + T cells were enriched with the CD4 + T Cell Isolation Kit (Miltenyi Biotec) according to the manufacturer's instructions. CD4 + T cells were cultured in Advanced RPMI 1640 (Corning) supplemented with 2 mM GlutaMAX (Gibco), 10% heat-inactivated FBS (Sigma-Aldrich, St. Louis, MO), and 100 U/mL penicillin-streptomycin.…”
Section: Primary Cd4 + T Cellsmentioning
confidence: 99%